The Influence of Marketing Strategy on Business Performance in the Sumedang Tofu Industry Moderated by Technology - Ani Anggraeni; Cupian Cupian; Wa Ode Zusnita Muizu (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2025)
This study aims to analyze the influence of marketing mix strategies on business performance in the Sumedang tofu industry. The background of the study departs from the phenomenon of declining performance of Sumedang tofu businesses in the last two years as indicated by a decline in sales, customers, and profits, despite this industry having a significant contribution to the local economy. The marketing mix strategy in this study covers seven dimensions, namely product, price, promotion, place, people, process, and physical evidence. The research method uses a non-experimental quantitative approach with data collection techniques through observation, interviews, and questionnaires with 284 Sumedang tofu business actors. Data analysis was carried out using the Structural Equation Modeling-Partial Least Square (SEM-PLS) method using SmartPLS software. Model evaluation was carried out through validity and reliability testing, as well as testing the structural model to determine the relationship between variables. The results show that marketing strategies have a positive and significant effect on business performance. This is indicated by a path coefficient value of 0.481, a t-statistic of 10.998, and a p-value of 0.000. These findings indicate that the more effective marketing strategy management, the higher the business performance, as reflected in sales growth, customer growth, and increased profits.